Engineered Remolding and Application of Bacterial Membrane Vesicles - Qiao, Li; Rao, Yifan; Zhu, Keting; Rao, Xiancai; Zhou, Renjie (Frontiers in Microbiology, 2021)
Bacterial membrane vesicles (MVs) are produced by both Gram-positive and Gram-negative bacteria during growth in vitro and in vivo. MVs are nanoscale vesicular structures with diameters ranging from 20 nm to 400 nm. MVs incorporate bacterial lipids, proteins, and often nucleic acids, and can effectively stimulate host immune response against bacterial infections. As vaccine candidates and drug delivery systems, MVs possess high biosafety owing to the lack of self-replication ability. However, wild-type bacterial strains have poor MV yield, and MVs from the wild-type strains may be harmful due to the carriage of toxic components, such as lipopolysaccharides, hemolysins, enzymes, etc. In this review, we summarize the genetic modification of vesicle-producing bacteria to reduce MV toxicity, enhance vesicle immunogenicity, and increase vesicle production. The engineered MVs exhibit broad applications in vaccine designs, vaccine delivery vesicles, and drug delivery systems.